Effect of fiber length on tensile strength, impact toughness, and flexural strength of Banana Stem Fiber (BSF)-polyester composite for train body - Balla Wahyu Budiarto; Willy Artha Wirawan; Fadli Rozaq; Natriya Faisal Rachman; Dhina Setyo Oktaria (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering))
The study aimed to determine the tensile and impact strength characteristics of the banana steam fiber (BSF)-polyester composite modified with NaOH treatment. The composites were made using the hand lay-up method, varying the length of the BSF fibers to 10 mm, 20 mm, and 30 mm. The fiber was modified by giving 2% NaOH for 1 day to improve the mechanical properties of the composite. The tensile strength tests were carried out using ASTM D638 standards. While impact tests were carried out using ASTM D6110 standards. The test showed the highest average tensile strength value at 30 mm fiber length, for 37.78 MPa. Meanwhile, the lowest value at 10 fiber length was 31.87 MPa. For the impact test, the highest average value was at 10 mm fiber length, for 0.016 J/mm2. And, the lowest value was at 30 mm fiber length variation, for 0.010 J/mm2. Fiber length has no significant effect on the flexural strength of the BSF composite.